Development of the life cycle inventory of masonry mortar made of natural and recycled aggregates. (1st January 2017) - Cuenca-Moyano, G.M.; Zanni, S.; Bonoli, A.; Valverde-Palacios, I.
Abstract: The use of recycled fine aggregate from construction and demolition waste as a replacement for natural fine aggregate in the manufacture of masonry mortar represents an environmental benefit that must be quantified. The life cycle assessment is a procedure that allows to know the environmental impacts associated with a product throughout its life cycle; for that purpose, it incorporates a series of phases of which inventory analysis is one of the most important as it directly influences its overall quality. The main aim of this study has been to develop the life cycle inventory of masonry mortars made of natural fine aggregate and recycled fine aggregate in accordance with ISO 14040 and ISO 14044, and being the system subject of study from cradle to gate level, thus boundaries included the production of the mortar components (natural fine aggregate, recycled fine aggregate, filler, cement and additive) and the production of masonry mortar in mortar plant. For the inventory development, production data given by the producers, Ecoinvent v.2.2 database and Environmental Product Declaration were used as data source. According to the results obtained, thanks to this study the main inputs regarding energy and raw material consumption and the main outputs (products, coproducts, waste and emissions) have been identified and quantified, linked to the masonry mortar life cycle and found inside the system boundaries considered. In a future research, the inventory developed shall allow to assess and compare the environmental impacts related to the production of masonry mortars made of natural fine aggregate and recycled fine aggregate. Highlights: The life cycle inventory of masonry mortar was developed. The main inputs and outputs were identified and assessed. Production processes of aggregates (natural and recycled) and mortar were defined. The study shall allow the impacts assessment related to masonry mortar life cycle.